Inappropriate medication use in older adults according to Beers Criteria in a Tertiary Referral Hospital, in Bolu, Turkey - Burcin M. Atak; Gulali Aktas; Tuba T. Duman; Ozge Kurtkulagi; Satilmis Bilgin; Gizem Kahveci; Muhammed E. Demirkol (Russian Open Medical Journal)
Aims — We aimed to study the medications used by older adults for any potentially inappropriate medications. Material and Methods — A hundred and four consecutive subjects over 65 years of age who visited our clinic were enrolled in the study. Possible inappropriate medications were defined according to Beers Criteria. Results — A total of 57 women and 49 men were enrolled in the study. Mean ages of the women and men were 78.6±6.1 years and 77.4±5.4 years, respectively (p=0.30). While 18 subjects (17%) had no increased risk due to inappropriate use of medications, 30 were on inappropriate medications that increased renal failure risk, 5 were on inappropriate medication that amplified neurological side effects, 12 were on inappropriate medications that augmented bleeding risk, 20 were on inappropriate medication that lack safety and efficacy data, and 30 were on inappropriate medication that amplified the risk of falls. The number of increased risks according to Beers Criteria was significantly and positively correlated with number of medications used (r=0.366, p<0.001) and the number of comorbidities (r=0.312, p=0.001). Conclusion — The number of increased risks due to inappropriate use of medicines in older adults is positively correlated with the number of medicines used and the number of accompanied diseases. Therefore we suggest that the medicines used by older people should be reviewed in all settings, and unnecessary drugs should be avoided to be prescribed.